KEKUATAN KLAUSULA BAKU TERHADAP PENJUALAN SMARTPHONE REKONDISI DITINJAU DARI UNDANG - UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Aisyah Nikita; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2021)
In Indonesia, consumers are protected by Law Number 8 of 1999 on Consumer Protection in order to strengthen the fairness of balance, security and consumer safety. Consumers, as weak parties, will experience losses if business actors include a default clause in buying and selling transactions. But there are still many consumers who accept the agreement by containing the default clause because of the need for these goods and / or services. Business actors in offering goods and / or services are expected to be wiser in including the default clause in a buying and selling transaction in accordance with what has been regulated in article 18 of UUPK. The consumer must also understand the rights that have been regulated in consumer protection laws so that he understands what actions can be taken by consumers if they experience losses incurred by business actors. Business actors can be held administratively liable with fines and criminally with prison sentences as well as additional fines and criminals in the form of confiscation of certain goods, announcement of judge's decision, payment of compensation, certain stop orders that harm consumers, obligations to withdraw products from circulation and revocation of business licenses. In this case, the business actor has no good faith and no responsibility for compensation for consumer losses due to the default clause in the transaction of buying and selling reconditioned smartphones The problem here is, how the strength of the default clause in the sale of reconditioned smartphones is reviewed from UUPK.